Performance Evaluation of Ad Hoc Routing Protocols for Military Communications - Christos Bouras; Apostolos Gkamas; G Kioumourtzis (International Journal of Network Management, Wiley InterScience, 2012)
Mobile Ad hoc networks (MANETs) are of much interest to both the research community and the military because of the potential to establish a communication network in any situation that involves emergencies. Examples are search-and-rescue operations, military deployment in hostile environment, and several types of police operations. One critical open issue is how to route messages considering the characteristics of these networks. The nodes act as routers in an environment without a fixed infrastructure, the nodes are mobile, the wireless medium has its own limitations compared to wired networks, and existing routing protocols cannot be employed at least without modifications. Over the last few years, a number of routing protocols have been proposed and enhanced to address the issue of routing in MANETs. It is not clear how those different protocols perform under different environments. One protocol may be the best in one network configuration but the worst in another. This article provides an analysis and performance evaluation of those protocols that may be suitable for military communications. The evaluation is conducted in two phases. In the first phase, we compare the protocols based on qualitative metrics to locate those that may be fit our evaluation criteria. In the second phase, we evaluate the selected protocols from the first phase based on quantitative metrics in a mobility scenario that reflects tactical military movements. The results disclose that there is no routing protocol in the current stage without modifications that can provide efficient routing to any size of network, regardless the number of nodes and the network load and mobility.